2017
DOI: 10.5194/acp-17-5677-2017
|View full text |Cite
|
Sign up to set email alerts
|

The radiative role of ozone and water vapour in the annual temperature cycle in the tropical tropopause layer

Abstract: Abstract. The structure and amplitude of the radiative contributions of the annual cycles in ozone and water vapour to the prominent annual cycle in temperatures in the tropical tropopause layer (TTL) are considered. This is done initially through a seasonally evolving fixed dynamical heating (SEFDH) calculation. The annual cycle in ozone is found to drive significant temperature changes predominantly locally (in the vertical) and roughly in phase with the observed TTL annual cycle. In contrast, temperature ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
(71 reference statements)
3
21
0
Order By: Relevance
“…This is broadly consistent with prior investigations of the influence of ozone in the TTL temperature cycle (Fueglistaler et al, 2011;Ming et al, 2017). This is broadly consistent with prior investigations of the influence of ozone in the TTL temperature cycle (Fueglistaler et al, 2011;Ming et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…This is broadly consistent with prior investigations of the influence of ozone in the TTL temperature cycle (Fueglistaler et al, 2011;Ming et al, 2017). This is broadly consistent with prior investigations of the influence of ozone in the TTL temperature cycle (Fueglistaler et al, 2011;Ming et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Time period used for ERA-I andMLS is 2005-2012. radiative heating. This effect was confirmed and further studied by Fueglistaler et al [2011], and recently extended to the radiative effects of water vapor by Gilford and Solomon [2017] and Ming et al [2017]. Gettelman et al [2009] showed that T CP in chemistry climate models (CCMs) is sensitive to the ozone amount in the TTL, which likely impacts their long-term trends in T CP .…”
Section: Introductionmentioning
confidence: 69%
“…Note that the radiative feedback due to the ozone seasonal cycle is strongest in spring and fall; i.e., our comparison between January and July only partially demonstrates this feedback. The radiative feedback due to the water vapor seasonal cycle likewise maximizes during spring and fall, with essentially no effect during January and July [ Gilford and Solomon , ; Ming et al , ]. The seasonal cycles in water vapor and ozone are in large parts produced by the seasonal cycle in upwelling [ Mote et al , ; Randel et al , ], as well as horizontal [ Konopka et al , ; Ploeger et al , ] and vertical [ Glanville and Birner , ] mixing; in that sense even the remaining seasonal temperature difference in SRE is of dynamical origin, albeit indirectly.…”
Section: Ttl In Local Radiative Equilibrium?mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional complication for understanding the annual cycle in O 3 is the feedback between ozone and upwelling by the residual circulation ( truew̄*) [ Andrews et al , ]. Changes in O 3 lead to changes in heating rates that impact the upwelling and then O 3 [ Ming et al , ]. Furthermore, changes in ozone heating rates would impact truew̄* indirectly through changes in wave‐induced forcing [ Ming et al , ].…”
Section: Introductionmentioning
confidence: 99%